Perceptions of agro-pastoralists towards the change in temperature and precipitation in the trans-Himalayan regions of Nepal - Aryal, S; Ghimire, S. K.; Dhakal, Y. R.; Gaire, N. P.; Bhandari, S. (Banko Janakari, 2017)
Climate change has emerged as a global concern despite its differential impacts across geographical, social and economic gradients. Understanding perceptions of local communities towards climate change is important as it advances the knowledge, and is the driver of autonomous adaptation and behavioral responses. The livelihood of the agro-pastoralists in the trans-Himalayan regions of Nepal depends on the natural resources, and is highly sensitive to the change in climatic variables. Although there are indications of pronounced climate change in terms of their important variables in the high-altitude compared to the lowland of Nepal, there is limited information on how communities living in those areas have perceived to the change. Realizing the significance of such information, perceptions of the agro-pastoralists towards the change in climatic variables were studied in the two important high- and trans-Himalayan districts- Dolpa and Mustang. The results of the study revealed that the perceptions of the agro-pastoralists correspond with the increasing trend of temperature and the changing (both increasing and decreasing) trends of precipitation. Moreover, the agro-pastoralists have perceived the decrease in snowfall and reported appearance of new forage and pasture species in rangelands. The findings will be useful to understand about the climate change in the high- and trans-Himalayan region, and to devise adaptation strategies in these areas. Banko Janakari, Vol. 27, No. 1, Page: 21-30